2016
DOI: 10.1155/2016/1659275
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Osteogenic Potential of Green Fluorescent Protein Labelled Human Embryonic Stem Cell‐Derived Osteoprogenitors

Abstract: Cellular therapy using stem cells in bone regeneration has gained increasing interest. Various studies suggest the clinical utility of osteoprogenitors-like mesenchymal stem cells in bone regeneration. However, limited availability of mesenchymal stem cells and conflicting evidence on their therapeutic efficacy limit their clinical application. Human embryonic stem cells (hESCs) are potentially an unlimited source of healthy and functional osteoprogenitors (OPs) that could be utilized for bone regenerative app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…They have also shown that the impairment of bone regeneration is probably due to a damage of the surrounding skeletal muscle (reviewed in Owston, Giannoudis, & Jones, ). For example, a recent study from Cao's laboratory (Islam et al, ) has shown that fluorescently labeled human embryonic stem cells‐derived osteoprogenitors (hESC‐OPs) are able to maintain both their GFP expression for the long term and their potential for osteogenic differentiation in culture. This will help in the future application of these fluorescently labeled hESC‐OPs in the noninvasive assessment of bone regeneration and therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…They have also shown that the impairment of bone regeneration is probably due to a damage of the surrounding skeletal muscle (reviewed in Owston, Giannoudis, & Jones, ). For example, a recent study from Cao's laboratory (Islam et al, ) has shown that fluorescently labeled human embryonic stem cells‐derived osteoprogenitors (hESC‐OPs) are able to maintain both their GFP expression for the long term and their potential for osteogenic differentiation in culture. This will help in the future application of these fluorescently labeled hESC‐OPs in the noninvasive assessment of bone regeneration and therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Cell tracking has been a focus of active research in regenerative engineering. , Enhanced green fluorescent protein (EGFP) reporter gene, , luciferase reporter gene, and 5-bromodeoxyuridine , are often used to image engineered cells. The luciferase and EGFP reporter genes, which have been used extensively in tumor cells, are rarely employed in implantology.…”
Section: Introductionmentioning
confidence: 99%
“…The green fluorescent protein (GFP)-MSCs/GFP-ECs differentiated from GFP-hESCs as reported 53 were cultured in PG/PGM and observed using an inverted laser scanning confocal microscope (Leica, Germany) at days 1, 3, 5, and 7. Serial optical sections were captured and reconstructed into 3D images, and the cell volume and sphericity were calculated using the Imaris 9.0.1 software (Bitplane, Switzerland).…”
Section: Methodsmentioning
confidence: 99%